Does Eating Vegetables at Start of Meal Prevent Childhood Overweight in Japan? A-CHILD Study - Tani, Yukako; Fujiwara, Takeo; Ochi, Manami; Isumi, Aya; Kato, Tsuguhiko (Frontiers in Pediatrics, 2018)
Background: Because eating behaviors are established early in life, it is important to instill healthy eating habits in children. However, no published studies have examined the effects of what is habitually consumed first at a meal on children's body weight in real settings. The aim of this study was to examine the associations between what was consumed (vegetables, rice/bread, meat/fish, or soup) at the start of a meal and childhood overweight in Japan. Methods: We used cross-sectional data from the Adachi Child Health Impact of Living Difficulty (A-CHILD) study, a population-based study comprising all first-grade students in Adachi City, Tokyo, Japan, performed in 2015. Through a questionnaire, we identified what types of food children ate first at meals. The questionnaire was completed by 4,040 caregivers. We used corresponding school health check-up data (height and weight) to assess overweight in each child. Results: The proportions of what was consumed first at a meal were 11.6%, 23.3%, 25.4%, 9.8%, and 29.9% for vegetables, meat/fish, rice/bread, soup, and undetermined (variable), respectively. Multivariate logistic regression showed the odds ratio of being overweight was 1.83 in children who ate meat/fish first (95% CI: 1.27-2.64, p <0.01) compared with children who ate vegetables first. In contrast, the odds ratios in children who consumed rice/bread or soup first compared with children who ate vegetables first were 1.18 (95% CI: 0.84-1.67, p = 0.34) and 1.30 (95% CI: 0.86-1.95, p = 0.21), respectively. Conclusion: Children who eat meat/fish at the start of a meal are more likely to be overweight than those who eat vegetables at the start of a meal. Future studies are needed to investigate the mechanisms of how the order in which food is consumed at a meal affects weight status in children.